2020
DOI: 10.21203/rs.3.rs-39510/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population migration, spread of COVID-19, and epidemic prevention and control: empirical evidence from China

Abstract: Background: This study applied the SEIR model to analyze and simulate the transmission mechanisms of the coronavirus disease 2019 (COVID-19) in China. Methods: The population migration was embedded in the SEIR model to simulate and analyze the effects of the amount of population inflow on the number of confirmed cases. Based on numerical simulations, this study used statistical data for the empirical validation of its theoretical deductions and discussed how to improve the effectiveness of epidemic prevention … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Transportation infrastructures mainly appeared in papers on a lower scale such as urban districts. On the state scale, the number of high-speed railways in China increased the number of cases ( Z. Hu et al, 2021 ), while Bayode et al (2022) reported no significant relationship between COVID-19 cases and international airports. On the county scale, in Zambia, the number of cases increased due to closeness to airports ( Phiri et al, 2021 ) but in the case of Germany and South Korea, the physical characteristics of transportation infrastructures were not significant factors ( Scarpone et al, 2020 ; Jo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Transportation infrastructures mainly appeared in papers on a lower scale such as urban districts. On the state scale, the number of high-speed railways in China increased the number of cases ( Z. Hu et al, 2021 ), while Bayode et al (2022) reported no significant relationship between COVID-19 cases and international airports. On the county scale, in Zambia, the number of cases increased due to closeness to airports ( Phiri et al, 2021 ) but in the case of Germany and South Korea, the physical characteristics of transportation infrastructures were not significant factors ( Scarpone et al, 2020 ; Jo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, commuting to work by bicycle and walking are also correlated with a lower number of cases in those neighborhoods ( Tribby and Hartmann, 2021 ; Guo et al, 2021 ; Wali and Frank, 2021 ). Worthy to mention that studies conducted in China showed that distance and connectivity to the pandemic epicenters, specifically Wuhan, are strong, significant and positive predictors of COVID-19 cases ( Z. Hu et al, 2021 ; Qiu et al, 2020 , Qiu et al, 2021 ; Lin et al, 2020 ; X.-D. Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In material and equipment security analysis, Ahmed et al constructed a decision-making model for major public health emergencies based on the spatial and temporal characteristics, key events, transmission dynamics, spatial distribution, infection scale, information characteristics, and medical resource dimensions [17]. Hu et al established observation indicators that signifcantly promoted the clarifcation of prevention and control priorities, achieved early warning efects, clarifed the reserve direction of emergency medical resources, and prevented the recurrence and spread of COVID-19 [18]. In terms of medical information system application, Asadzadeh et al proposed the diferent efects and intrinsic mechanisms of direct and indirect applications of medical information systems on the quality of clinical treatment services and the quality of doctor-patient communication [19].…”
Section: Public Health Emergencymentioning
confidence: 99%
“…As to environmental factors, a study indicated temperature and the columnar density of total atmospheric ozone had a strong association with the tendency of COVID-19 spreading in almost all states in the USA [54]. As for regulations mainly including mobility restrictions and other non-pharmacological interventions, ill-prepared work [55], facemask shortage [56], poor traveller screening [57], forgone care [58], and population migration [59] could lead to ineffective prevention and controlling COVID-19. Regarding progressing stages, changes of COVID-19 ND, NH, NR, and NC might be caused by COVID-19 epidemic progressing laws differentially in various countries.…”
Section: Main Outcomesmentioning
confidence: 99%